Interchangeability of player movement variables from different athlete tracking systems in professional soccer - Ellens, S.; Hodges, D.; McCullagh, S.; Malone, J. J.; Varley, M. C. (Science and Medicine in Football, 2022)
This study assessed the interchangeability between 10-Hz multi-GNSS GPS devices (Vector®) and two optical tracking systems (TRACAB® and Second Spectrum®). The agreement between data from the optical tracking systems when processed with manufacturer and GPS-filtered software was also assessed. Thirty players competing in the English Premier League were monitored using three different tracking systems across five matches. To determine the interchangeability between systems, player movement variables including, total distance, high-speed running distance (19.8-25.2 km·h-1), sprinting distance (>25.2 km·h-1), efforts >19.8 km·h-1 and maximal speed were compared. Equations were formed using linear regression and linear mixed-effects models to allow interchangeability of player movement variables between systems. Over half of the variance of most interchangeability equations were explained and associated with very strong positive correlations (r > 0.72). Small to huge differences were found between systems for most player movement variables. Data of optical tracking systems had decreased values in speed variables >19.8 km·h-1 when processed through GPS software. This study provides equations for practitioners to interchange player movement variables between TRACAB, Second Spectrum and Vector GPS systems with reduced error. This will enable practitioners to combine and share data captured with different tracking systems to analyse and improve their training.